Beneficiary Population Analysis of Curative Care Expenditure in Community Health Service Institutions before and after Comprehensive Medical Reform in Beijing - JIANG Yan, MAN Xiaowei, ZHAO Liying, CHENG Wei (Zhongguo quanke yixue, 2024)
Background It is of great significance to clarify the characteristics of the main population served by community health service institutions for the precise reform of community health service institutions in the next step. Objective To provide accurate data support for the next reform policy formulation and adjustment by analyzing the characteristics of the beneficiary population in terms of curative care expenditure (CCE) in community health service institutions in Beijing before and after the comprehensive reform. Methods The basic data of this study was obtained from the basic database of total health expenditure accounting in Beijing from 2016 to 2019, and other data was obtained from Beijing Health Statistical Yearbook, Beijing Health Financial Statistics Annual Report, and Beijing Health Expenditure Accounting Report from 2016 to 2019. The multi-stage stratified cluster sampling was adopted to select community health service institutions, and the annual out-patient data and in-patient data were included from HIS system. System of Health Accounts 2011 (SHA 2011) was used to calculate and analyze the situation of the beneficiaries of community health service institutions. Results The CCE of community health service institutions in Beijing increased from 12.181 billion yuan to 22.245 billion yuan with an average annual increase of 19.07% from 2016 to 2019. The CCE of middle-aged and elderly patients over 40 years age accounted for more than 92% over the years, and CCE of patients in the age groups of 60s and 80s increased rapidly, with an average annual growth rate of 24.08% and 25.84%, respectively. Among the CCE, endocrine, nutritional and metabolic diseases, abnormal symptoms, signs and test results, circulatory system diseases accounted for the highest proportion. The CCE of endocrine, nutritional and metabolic diseases, nervous system diseases, abnormal symptoms, signs and test results increased rapidly, with an average annual growth rate of 40.11%, 48.40% and 32.43%, respectively. Conclusion The effectiveness of hierarchical diagnosis and treatment has begun to emerge after the comprehensive reform. Community medical service resources in Beijing are mainly consumed by middle-aged and elderly patients and patients with chronic non-communicable diseases such as endocrine and circulatory diseases. The comprehensive reforms guided more middle-aged and elderly people and patients with chronic diseases to community health service institutions. Community health service institutions should improve their service capacities in many aspects, such as service capacity, human resource, chronic disease management and medical consortium construction, to consolidate and maintain the effectiveness of the reform.